1968
DOI: 10.1136/gut.9.4.420
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying rate of the water and fat phases of a mixed test meal in man.

Abstract: Most reported studies of gastric emptying in humans have been concerned primarily with the regulation of pyloric passage of a single-phase meal. However, Wiggins and Dawson (1961) sampled intestinal contents in man after ingestion of a mixed meal, and found that the proportions of fat and water recovered were different from those of the meal. Harkins, Longenecker, and Sarett (1964) observed in rats that the fat and water phases do not leave the stomach in parallel, fat being retained longer. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…This finding of faster gastric emptying of the aqueous phase confirms the finding of earlier workers [Wiggins & Dawson, 1961;Chang, McKenna and Beck, 1968;Harkins, Longenecker and Sarett, 1969]. However, there was a slight but consistent excess of triether over 14C activity in the gastric contents.…”
Section: Discussionsupporting
confidence: 91%
“…This finding of faster gastric emptying of the aqueous phase confirms the finding of earlier workers [Wiggins & Dawson, 1961;Chang, McKenna and Beck, 1968;Harkins, Longenecker and Sarett, 1969]. However, there was a slight but consistent excess of triether over 14C activity in the gastric contents.…”
Section: Discussionsupporting
confidence: 91%
“…This may be because in subjects with an intact stomach, sitting erect as was usual during the test, 47Ca C12 may not enter the small intestine at the same time as the fat. Different rates of emptying of the lower aqueous and upper lipid phases of a mixed meal have been observed (Wiggins and Dawson, 1961;Chang, McKenna, and Beck, 1968). In patients with rapid gastric emptying, the fats will be more likely to enter the small intestine mixed with the 47Ca Cl2 and other components of the aqueous phase of the meal.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with rapid gastric emptying, the fats will be more likely to enter the small intestine mixed with the 47Ca Cl2 and other components of the aqueous phase of the meal. In normal subjects, on the other hand, the '7Ca Cl2 in the aqueous component ofthe meal might be expected to enter the small intestine and be at least partly absorbed before the fat had left the stomach (Chang et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by methodological problems in labelling fats because most dietary fats are liquefied at room temperature. In normal subjects, fat empties more slowly than liquids [12,13], whereas extracellular fat seems to empty as an oil phase at a rate similar to an equicaloric digestible solid meal [14]. The mechanisms for these observations are still unknown, but it has been suggested that the slower emptying of fats may be due to the formation of a layer of oil on top of the liquid phase of the meal as a consequence of gravity [13].…”
Section: Introductionmentioning
confidence: 99%
“…In normal subjects, fat empties more slowly than liquids [12,13], whereas extracellular fat seems to empty as an oil phase at a rate similar to an equicaloric digestible solid meal [14]. The mechanisms for these observations are still unknown, but it has been suggested that the slower emptying of fats may be due to the formation of a layer of oil on top of the liquid phase of the meal as a consequence of gravity [13]. However, although gravity may have a major effect on the intragastric distribution of oil, there is relatively little effect on total stomach emptying of oil [15].…”
Section: Introductionmentioning
confidence: 99%